(untitled) (REMUNOM, 2025)
Abstract Dental caries is a significant public health problem, being the most common disease in children and adults, in addition to representing the main cause of tooth loss. With advances in dental research and the introduction of minimally invasive techniques, lasers have become an increasingly used tool by dentists. The high-power Er:YAG (Erbium-Yttrium-Aluminum-Garnet) laser stands out for preserving tooth structure and reducing patients’ fear and pain during caries removal, compared to traditional methods. This laser, widely used in the treatment of caries, allows the selective removal of hard tissue through ablation. Laser therapy offers several applications in dentistry, being widely used in cariology for the prevention, diagnosis and treatment of caries, bringing significant benefits to the general health of patients. The objective of this review is to clarify doubts about the use of high-power laser in the removal of carious tissue and in the preparation of dental cavities in dental clinics. Keywords: Dentistry; laser therapy; dental caries.